Early specialisation in young gymnasts: a mixed methods study protocol - Evert Verhagen; Caroline Bolling; Félix Croteau; Joseph Baker; Margo Lynn Mountjoy; Justine Benoit-Piau; Yannick Hill (BMJ Open Sport & Exercise Medicine)
Over the past few decades, we have seen an increase in the popularity of organised sports among youth, especially gymnastics. Along with this increase in the popularity of organised sports, sports specialisation is also on the rise. Some argue that specialising as early as possible is essential for better performance and skill development. However, it has been associated with negative mental health effects in children and adolescents, as well as a higher risk of overuse injuries in young athletes. Although sports specialisation has been a popular research topic in recent years, many questions regarding its underlying factors and its impacts (positive or negative) on injuries, psychosocial health and performance remain unanswered. The purpose of this study is to present the protocol for a study that aims to describe sports specialisation in young gymnasts and to understand the association between sports specialisation, injury, psychological health and physical performance. This study will use a convergent mixed methods design. There will be a qualitative phase where we will conduct interviews and focus group discussions with athletes and different actors in the field. This will be conducted alongside a prospective cohort study over an entire sports season. Athletes will be assessed at the start, middle and end of the season for skill acquisition (core strength and endurance, power and dynamic postural control), psychosocial variables (stress, personality traits, anxiety and quality of life) and sports participation. They will be followed throughout the season using online weekly surveys to monitor training load and injuries.